Beyond the screen: unfolding digital finance usage through a gendered lens during and after COVID-19 - Meenakshi P.; Satish Kumar; Sowjanya Shetty (Cogent Economics & Finance)
Understanding the determinants of digital financial service adoption and gender disparities is crucial for fostering inclusive growth. This study aims to investigate the factors influencing the shift in the usage of digital financial products and services in India with a focus on addressing the gender divide in their adoption. The analysis is carried out through pooled logit regression and fairly decomposition technique, with the data processed through STATA-18 software. To this end, India's micro-level data were pooled from the Global Findex Database for the years 2017 and 2021, with a sample size of 3,000 for each year. The results indicate a substantial increase in nearly all forms of digital transactions since the pandemic, with notable increases in mobile usage and online banking, excluding government transfers. Additionally, socioeconomic factors, such as education, income, and workforce participation, along with the ownership of digital financial products, have significantly contributed to the adoption of digital financial products and services. Despite this increase, there has been a widening gender gap in the adoption of digital financial services over the years. This is primarily influenced by women's low literacy and low access to digital financial products. Future research could benefit from qualitative studies exploring the underlying reasons for the persistent gender disparity in digital finance usage.